2005
DOI: 10.1029/2004gl021942
|View full text |Cite
|
Sign up to set email alerts
|

Organic reactions increasing the absorption index of atmospheric sulfuric acid aerosols

Abstract: [1] Unlike most environments present at Earth's surface atmospheric aerosols can be favorable to organic reactions. Among them, the acid-catalyzed aldol condensation of aldehydes and ketones produces light-absorbing compounds. In this work the increase of the absorption index of sulfuric acid solutions 50-96 wt. % resulting from the uptake of gas-phase acetaldehyde, acetone, and 2-butanone (methyl ethyl ketone), has been measured in the near UV and visible range. Our results indicate that the absorption index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 17 publications
1
64
1
Order By: Relevance
“…While hexanal has no absorption features in the visible region, the long wavelength edge of the aldol spectrum extends into the visible region, leading to the observed yellow color of the product solution. This characteristic has been attributed to polymerization by others (Limbeck et al, 2003;Noziere and Esteve, 2005;Zhao et al, 2005). For example, Noziere and Esteve (2005) have suggested in the acid-catalyzed reaction of acetaldehyde the appearance of a product peak at 350 nm is due to the formation of three conjugated double bonds, which would occur if three acetaldehyde molecules reacted.…”
Section: Optical Propertiesmentioning
confidence: 97%
See 3 more Smart Citations
“…While hexanal has no absorption features in the visible region, the long wavelength edge of the aldol spectrum extends into the visible region, leading to the observed yellow color of the product solution. This characteristic has been attributed to polymerization by others (Limbeck et al, 2003;Noziere and Esteve, 2005;Zhao et al, 2005). For example, Noziere and Esteve (2005) have suggested in the acid-catalyzed reaction of acetaldehyde the appearance of a product peak at 350 nm is due to the formation of three conjugated double bonds, which would occur if three acetaldehyde molecules reacted.…”
Section: Optical Propertiesmentioning
confidence: 97%
“…This characteristic has been attributed to polymerization by others (Limbeck et al, 2003;Noziere and Esteve, 2005;Zhao et al, 2005). For example, Noziere and Esteve (2005) have suggested in the acid-catalyzed reaction of acetaldehyde the appearance of a product peak at 350 nm is due to the formation of three conjugated double bonds, which would occur if three acetaldehyde molecules reacted. In this study, 1 H-NMR data indicates that no polymerization has occurred in the aldol condensation reaction of hexanal, implying that the conjugation in the aldol condensation product alone accounts for the color of the product.…”
Section: Optical Propertiesmentioning
confidence: 97%
See 2 more Smart Citations
“…A recent modeling study has investigated the role of dicarboxylic acids in atmospheric ice formation and found that changes in water uptake can affect the size of particles containing organics and thus can explain the observations that organic containing particles are less efficient at ice nucleation (Kärcher and Koop, 2005). While ice nucleation has mainly been studied for mixtures of dicarboxylic acids with ammonium sulfate, other carbonyl-containing compounds, such as aldehydes and ketones, have been investigated at warmer temperatures to probe acid-catalyzed reactions with sulfuric acid (Iraci and Tolbert, 1997;Jang et al, 2002;Nozière and Riemer, 2003;Michelsen et al, 2004;Garland et al, 2006;Liggio et al, 2005;Nozière and Esteve, 2005;Zhao et al, 2005). An important characteristic of these acid-catalyzed reactions is the ability to form products of lower vapor pressure and solubility as well as higher melting points than the initial reactant compounds.…”
Section: Introductionmentioning
confidence: 99%